Pluralism - Lassman, Peter (Malden, MA : Polity, 2011)
The problem of value pluralism permeates modern political philosophy. Its presence can be felt even when it is not explicitly the central topic under investigation. Political thinkers such as Max Weber, Isaiah Berlin and Stuart Hampshire derive pessimistic, sometimes tragic, conclusions from their reflections upon pluralism.
Includes bibliographical references (p. [167]-183) and index.
Keywords: Political science -- Philosophy; Pluralism